Pemasaran Jasa Pendidikan Sebagai Strategi Peningkatan Mutu Pendidikan Di Perguruan Tinggi Islam - Hidayatussaliki, Hidayatussaliki; Alfian, Riki; Ma’sum, Afif (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The article discusses the challenges and problems experienced by Islamic Higher Education. In order to face these challenges and problems, a strategy is needed as a tool to gain competitive advantage. This article aims to clarify the strategy in marketing educational services as a strategy to improve the quality of education in Islamic tertiary institutions. This article uses a type of qualitative research with a type of library research, by collecting literature or materials sourced from books, journals and other related sources. PTI's service marketing strategy consists of 6 strategies in which these six strategies are not a sequence that reflects the stages of the steps, but a single strategy that can be carried out simultaneously or separately, including: SWOT analysis, identification of consumers and their needs, utilization of marketing channels and models, optimizing PTI's marketing agency, building public trust, and marketing mix. Meanwhile, measuring the level of customer satisfaction with the services offered by educational institutions can be carried out in the following ways: Complaint and suggestion system, Customer satisfaction surveys, Ghost shopping, Lost customer analysis customer analysis who switch.